The influence of fluoxetine on orthodontic tooth movement in rats - Gabriela Costa MARIN; Aline Cristina Batista Rodrigues JOHANN; Isteicy Cortêz SILVA; Ana Carolina Mastriani ARANTES; Ana Maria Trindade Grégio HARDY; Sergio Aparecido IGNÁCIO; Orlando Motohiro TANAKA; Odilon GUARIZA FILHO; Elisa Souza CAMARGO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study aimed to evaluate the effects of chronic use of fluoxetine on the amount of orthodontic tooth movement and tissue changes in rats. A total of 192 Wistar rats were divided into 4 groups: S, 0.9% saline solution; F, 20 mg/kg of fluoxetine; SM, 0.9% saline solution with orthodontic movement; and FM, 20 mg/kg of fluoxetine with orthodontic movement. After 30 days of daily saline or fluoxetine administration, an orthodontic device (25cN) was used to mesially displace the first molar in animals of the groups SM and FM. The animals were euthanized 2, 7, 14, and 28 days after placement of the orthodontic appliances and animals of groups S and F were euthanized at the same time. The assessment of tooth movement was made in gypsum castings, the collagen neoformation was assessed by polarization microscopy, the number of osteoclasts and root resorption were evaluated using tartrate-resistant acid phosphatase, and presence of hyalinized areas was assessed by hematoxylin-eosin staining. Fluoxetine did not affect the amount of tooth displacement, percentage of collagen, number of osteoclasts, and presence of hyalinized areas (P>0.05). There was a higher frequency of root resorption areas in the FM group than in the SM group only on the second day (P<0.05). The findings of this study show that chronic use of 20 mg/kg fluoxetine does not affect the amount of tooth movement, collagen neoformation, number of osteoclasts, or hyalinized areas and does not affect root resorption until the last day of orthodontic movement.